Dental Immunisation: Evaluation of a Community-Driven Strategy for Addressing Caries Burden in Indonesian School Children - Irene Adyatmaka; Jilen Patel (Journal of the California Dental Association)
Background The World Health Organization (WHO) has long emphasized the significance of oral health as a key component of overall health and well-being. Global oral health disparities, often exacerbated by a lack of access to essential dental care, present a challenge that resonates on a worldwide scale.Aims This study explores how community-driven strategies can actively support the global oral health goals set forth by the WHO.Methods The RE-AIM framework was applied to evaluate a “Dental Immunisation” program in Bali, Indonesia. An evaluation of the Reach, Effectiveness, Adoption, Implementation, and Maintenance of the program was conducted.Results Dentists collaborated with local communities to co-create oral health initiatives targeting school children and their families. A total of 210 children from two schools were enrolled in the program, with a mean age of 9.4 years. Collaborative oral health workshops with local staff and families amplified the impact of school-based initiatives with 50 parents and teachers also participating in oral health promotion activities. At baseline, 60% of Grade 1 children presented with carious lesions, averaging 2.3 affected teeth per child. No children had previously received any restorative care. Post-intervention, 150 teeth were restored using ART, with all participants receiving toothbrushes and application of fluoride varnish.Conclusion The “Dental Immunisation” program demonstrates a potential paradigm shift in community-based dental care and prevention strategies. By bridging local practices with global objectives, a more interconnected and collaborative approach to tackling oral health disparities may be achieved. Ongoing longitudinal studies will be essential to validate and expand on the findings from this project.